ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, LEVERAGE DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN SEKTOR ENERGI - Sumilir Sumilir; Mohamad Katami Aji Saputra; Yudi Nur Supriadi (Gapenas Publisher, 2023)
This study aims to determine the effect of Corporate Social Responsibility proxied with CSR funds, Profitability proxied with Return On Asset (ROA), Leverage proxied by Debt to equity Ratio (DER) and Activity proxied by Inventory Turnover (ITO) toward Firm Value proxied by Price to Book Value (PBV). Population in this study are energy companies listed on Indonesia Stock Exchange (IDX) 2017-2021. The technique of determination of the sample using the method of purposive sampling and obtained 37 sector energy companies with a research period of five years. Hypothesis testing in this research using Data Panel Regression Analysis with E-Views 12.0 program and significance level of 5%. The result of the research shows that (1) corporate social responsibility (CSR funds) no significant effect on firm value (PBV), (2) profitability (ROA) has a significant positive effect on firm value (PBV), (3) Leverage (DER) has significant positive effect on firm value (PBV), (4) activity (ITO) no significant effect on firm value (PBV),